Development and Implementation of a Self-Management Intervention Program for Patients with Esophageal and Gastric Varices Secondary to Liver Cirrhosis Under Collaborative Care - Li M; Xie XE; Qin X; Wu T; Bian ZL (International Journal of General Medicine)
Ming Li,1,2 Xing-Er Xie,3 Xiangqing Qin,2 Tian Wu,2 Zhao-Lian Bian2 1School of Nursing and Rehabilitation, Nantong University, Nantong, 226000, People’s Republic of China; 2Department of Gastroenterology, the Third Affiliated Hospital of Nantong University, Nantong, 226000, People’s Republic of China; 3Department of Nursing, the Third Affiliated Hospital of Nantong University, Nantong, 226000, People’s Republic of ChinaCorrespondence: Xing-Er Xie, Email ardf411@163.comObjective: To design and evaluate a self-management intervention program tailored for patients undergoing endoscopic treatment for esophageal and gastric varices secondary to liver cirrhosis, implemented within a collaborative care framework.Methods: The control group received standard inpatient care and discharge instructions, whereas the intervention group participated in the newly developed collaborative care program. Key outcomes, including self-management proficiency, medication adherence, quality of life, rebleeding rates, and unplanned readmissions within a three-month period, were compared between the two groups. Subgroup analyses were conducted based on disease severity using Child-Pugh scores.Results: The intervention group demonstrated significantly higher scores in self-management proficiency compared to the control group (P < 0.05). Medication adherence was markedly better in the intervention group (P < 0.05), with a 95% adherence rate versus 76.92% in the control group. Quality of life assessments also revealed superior scores in the intervention group (P < 0.05). Additionally, the intervention group had significantly lower rates of unplanned readmissions (5.00% vs 20.51%, P < 0.05) and rebleeding (10.00% vs 30.77%, P < 0.05) compared to the control group. The 12-month survival rate was significantly higher in the intervention group (95.00% vs 79.49%, P < 0.05). Subgroup analyses indicated that patients with more advanced disease benefited the most from the intervention.Conclusion: The implementation of a self-management intervention program within a collaborative care framework significantly enhances self-management capabilities, medication adherence, and quality of life while reducing rebleeding rates, unplanned readmissions, and mortality in patients with esophageal and gastric varices secondary to liver cirrhosis. These findings underscore the importance of tailored self-management strategies, particularly for patients with advanced disease, and highlight the potential of collaborative care to address the complex needs of this population. This study provides a strong foundation for future research to optimize and scale similar interventions in diverse clinical settings.Keywords: Endoscopic treatment, esophageal and gastric varices, liver cirrhosis, self-management, collaborative care, intervention